Cost-effectiveness of intravitreal therapy in Age-Related Macular Degeneration - Neri, Piergiorgio; Arapi, Ilir; Eandi, Chiara Maria; Pirani, Vittorio; Mariotti, Cesare; Giovannini, Alfonso (Farmeconomia. Health economics and therapeutic pathways, 2014)
Age-related macular degeneration (AMD) is still referred to as the leading cause of severe and irreversible visual loss world-wide. Advances in medical research have identified vascular endothelial growth factor (VEGF) as an important pathophysiological player in neovascular AMD and intraocular inhibition of VEGF as one of the most efficient therapies. Anti-VEGFs currently used to treat AMD included a monoclonal antibody (bevacizumab), an antibody fragments (ranibizumab), a fusion protein (aflibercept), and an aptamer (pegaptanib). The wide introduction of anti-VEGF therapy has led to an improvement in the prognosis of patients affected by AMD, with a consequent effects on the burden of care due to highly priced drugs, increasing patient numbers, and long-term disease chronicity. Aim of this review is to present an overview of available therapeutic strategies in AMD in term of clinical efficacy and economic sustainability.